To solve for x, first we need to get all the x terms on one side of the equation and the constant terms on the other side.
Given equation: 3x - 3 = 6x + 18
Let's move the x term to one side by subtracting 6x from both sides:
3x - 3 - 6x = 6x + 18 - 6x
Simplifying both sides:
-3x - 3 = 18
Now, move the constant term to the other side by adding 3 to both sides:
-3x - 3 + 3 = 18 + 3
Simplifying both sides:
-3x = 21
Finally, solve for x by dividing both sides by -3:
x = 21 / -3
x = -7
Therefore, x = -7 is the solution.
Solve for x : 3x−3=6x+18 .(1 point)
5 answers
Solve for x : 4x+8=3x−10 .(1 point)
To solve for x, first we need to get all the x terms on one side of the equation and the constant terms on the other side.
Given equation: 4x + 8 = 3x - 10
Let's bring all the x terms to one side by subtracting 3x from both sides:
4x + 8 - 3x = 3x - 10 - 3x
Simplifying both sides:
x + 8 = -10
Now, move the constant term to the other side by subtracting 8 from both sides:
x + 8 - 8 = -10 - 8
Simplifying both sides:
x = -18
Therefore, x = -18 is the solution.
Given equation: 4x + 8 = 3x - 10
Let's bring all the x terms to one side by subtracting 3x from both sides:
4x + 8 - 3x = 3x - 10 - 3x
Simplifying both sides:
x + 8 = -10
Now, move the constant term to the other side by subtracting 8 from both sides:
x + 8 - 8 = -10 - 8
Simplifying both sides:
x = -18
Therefore, x = -18 is the solution.
Solve for x : 13x+26=3x−34 .(1 point)
To solve for x, we need to get all the x terms on one side of the equation and the constant terms on the other side.
Given equation: 13x + 26 = 3x - 34
Subtract 3x from both sides to move all x terms to the left side:
13x + 26 - 3x = 3x - 34 - 3x
Simplify both sides:
10x + 26 = -34
Next, move the constant term to the right side by subtracting 26 from both sides:
10x + 26 - 26 = -34 - 26
Simplify both sides:
10x = -60
Divide by 10 on both sides to solve for x:
x = -60 / 10
x = -6
Therefore, x = -6 is the solution.
Given equation: 13x + 26 = 3x - 34
Subtract 3x from both sides to move all x terms to the left side:
13x + 26 - 3x = 3x - 34 - 3x
Simplify both sides:
10x + 26 = -34
Next, move the constant term to the right side by subtracting 26 from both sides:
10x + 26 - 26 = -34 - 26
Simplify both sides:
10x = -60
Divide by 10 on both sides to solve for x:
x = -60 / 10
x = -6
Therefore, x = -6 is the solution.